A biophysical and economic evaluation of biological and chemical control methods for Solanum elaegnifolium (Silverleaf Nightshade) in the Limpopo province, South Africa - Pitso, Dikeledi Confidence (Department of Biological Sciences, 2015)
Includes abstract.